Understanding responses to posted restaurant food safety scores: An information processing and regulatory focus perspective. (January 2017) - Harris, Kimberly J.; Hanks, Lydia; Line, Nathaniel D.; McGinley, Sean
Abstract: Ensuring the safety of food served in restaurants continues to be an essential issue in the hospitality industry. An important part of the efforts to stem the outbreak of foodborne illnesses are the mandatory inspections of any entity that serves food to the public. Unfortunately, while posting food safety scores is intended to help consumers make better dining choices, interpreting these scores can often be difficult and confusing. The purpose of this study is to use information processing theory as a framework to investigate how consumers evaluate food safety inspection scores. To achieve this goal, this research provides an account of the effect of food safety concern on consumers' attitudes toward restaurants under conditions of both positive and negative health inspection results. The results identify a moderating effect of health score in the formation of consumers' attitudes toward restaurants. The downstream effects on expected satisfaction and behaviors are also established.